The Evolution of Rules, Markets and Culture-based Control III an Organizational Setting: A Case Study - Bakar, Mohamad Adam; Berry, Anthony J. (Universiti Putra Malaysia Press, 1995)
This paper focuses on the issue of rules. markets and culture as bases of control. In particular, it seeks to address the question of how does the management c0ntrol system (MICS) of an organization change Over time" .A. television company in the UK provided the selling for the study, and empirical data were gathered during 18 month of field research. From the evidence gathered we were able to suggest that the MCS evolved towards increasing reliance on rules and markets and not controls based (}11 organizational culture.